Construction et restructuration territoriale chez les Wayãpi et Teko de la commune de Camopi, Guyane française - Davy Damien; Isabelle Tritsch; Pierre Grenand (Confins)
Two peoples of Tupi-Guarani language, Teko and Wayãpi Indians, live on the territory of Camopi, French Guiana municipality. In this article we try to trace the historical construction of the present territories of these people by showing how and when they appropriate it. We explain how these territories have become a municipality of the French Republic. In a second part, we present how these people adapt to contemporary changes induced by illegal mining taking place on their territory and to an unprecedented demographic increase of theirs own peoples. Finally, after showing the failure of reunification policies that the French state has imposed since 40 years, we conclude on the importance of the identity claims for their land and their cultures.